2016
DOI: 10.1002/14651858.cd008824.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation for preventing infections in children under five years of age

Abstract: Background Vitamin D is a micronutrient important for bone growth and immune function. Deficiency can lead to rickets and has been linked to various infections, including respiratory infections. The evidence on the effects of supplementation on infections in children has not been assessed systematically. Objectives To evaluate the role of vitamin D supplementation in preventing pneumonia, tuberculosis (TB), diarrhoea, and malaria in children under five years of age. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
99
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 129 publications
0
99
0
2
Order By: Relevance
“…The wide pleiotropism of this natural hormone vitamin, which can be considered similar to other diet-derived plant polyphenols, antioxidants, and additional nutritional supplements, 1 is disconcerting, compared with the high frequency of deficient levels of circulating vitamin D in the human population. [2][3][4][5] Despite its importance, people seem to live perfectly with apparently long-lasting deficiencies of vitamin D. Vitamin D is an ancient hormonal molecule; it is photosynthesized in all forms of life, starting from the phytoplankton ( 750 million years ago) to mammals and humans. 6 For certain aspects, vitamin D might be selected as one of the first natural antioxidant prohormones from nonplant-derived foods, and thus cells were instructed to synthesize it.…”
Section: Introductionmentioning
confidence: 99%
“…The wide pleiotropism of this natural hormone vitamin, which can be considered similar to other diet-derived plant polyphenols, antioxidants, and additional nutritional supplements, 1 is disconcerting, compared with the high frequency of deficient levels of circulating vitamin D in the human population. [2][3][4][5] Despite its importance, people seem to live perfectly with apparently long-lasting deficiencies of vitamin D. Vitamin D is an ancient hormonal molecule; it is photosynthesized in all forms of life, starting from the phytoplankton ( 750 million years ago) to mammals and humans. 6 For certain aspects, vitamin D might be selected as one of the first natural antioxidant prohormones from nonplant-derived foods, and thus cells were instructed to synthesize it.…”
Section: Introductionmentioning
confidence: 99%
“…Different immunomodulatory effects may explain these associations (5). Moreover, despite convincing in vitro findings, there are examples of observational studies finding no associations (6), and clinical trials and reviews have been inconclusive about the role of vitamin D (7,8). These inconsistent findings have led to a discussion on whether hypovitaminosis D is a cause or a consequence of inflammation (9,10).…”
mentioning
confidence: 99%
“…Among the preventive systematic reviews, five focused on healthy individuals for prevention of death, 16 cancer, 14 and other adverse outcomes. 12,25,27 Despite the considerable number of Cochrane reviews, eight of them did not present any reliable evidence regarding benefits or harm from vitamin D, including reviews on clinical situations in which use of vitamin D is frequently observed in clinical practice, such as in relation to multiple sclerosis 9 and atopic eczema. 7 Thus, in those reviews, the authors were unable to provide recommendations regarding the benefits and risks of vitamin D. A second point that deserves discussion is that many of the reviews included were planned, conducted or published some years ago, and therefore were based on early versions of the Cochrane Handbook, which were less detailed and complex than the current version (http:// training.cochrane.org/handbook).…”
Section: Discussionmentioning
confidence: 99%